Parent and adolescent communication with healthcare professionals about Type 1 diabetes management at adolescents' outpatient clinic appointments. Issue 5 (25th July 2019) - Rawdon, C.; Gallagher, P.; Glacken, M.; Swallow, V.; Lambert, V.
Abstract: Aim: This study aimed to identify the ways in which adolescents living with Type 1 diabetes and their parents communicate about Type 1 diabetes management with healthcare professionals in a clinical setting. Methods: Twenty‐nine adolescents (aged 11–17 years) and their parents were purposively recruited from two outpatient clinics for non‐participant observations. Outpatient clinic appointments, which consisted of multiple consultations with healthcare professionals, were observed and audio‐recorded. Outpatient clinic appointments were categorized based on the nature and extent of communication by the adolescent and their parent(s) in relation to Type 1 diabetes management activities. Results: Data from 29 outpatient clinic appointments, consisting of a total of 68 observed consultations, were analysed and a continuum consisting of three patterns of communication was identified (parent‐led, collaborative and adolescent‐led). Healthcare professionals should attend to the nature and extent of communication by adolescents and their parents in relation to Type 1 diabetes management activities because parent and adolescent engagement in communication during clinic appointments may also reflect their degree of involvement in daily Type 1 diabetes management. Conclusions: This continuum provides a framework for healthcare professionals to use to identify communication patterns in consultations which in turn may allow healthcare professionals to encourage more effective communication about Type 1 diabetes management from adolescents and their parents in clinic consultations. This may have a positive impact on the sharing of Type 1 diabetes management responsibilities and adolescents' developing self‐management skills as roles change during this developmental period. What's New?: Outpatient clinic appointments with 29 adolescents living with Type 1 diabetes and their parents were observed to examine how adolescents and their parents communicate about Type 1 diabetes management with healthcare professionals in a clinical setting. Three patterns of communication were identified (parent‐led, collaborative and adolescent‐led). Parent and adolescent engagement in communication with healthcare professionals during outpatient clinic appointments may reflect their degree of involvement in daily Type 1 diabetes management. By attending to the nature and extent of communication to healthcare professionals by adolescents and/or their parents, healthcare professionals may be able to encourage more effective communication in consultations and support adolescents as their self‐management skills develop.